Relationships and gender differences within and between assessments used in Swedish home rehabilitation - a cross-sectional study - Anette Johansson; Cristina Joy Torgé; Sofi Fristedt; Marie Ernsth Bravell (BMC, 2022)
Abstract Background Home rehabilitation programmes are increasingly implemented in many countries to promote independent living. Home rehabilitation should include a comprehensive assessment of functioning, but the scientific knowledge about the assessment instruments used in this context is limited. The aim of this study was to explore relationships between standardised tests and a self-reported questionnaire used in a home rehabilitation programme. We specifically studied whether there were gender differences within and between assessments. Method De-identified data from 302 community-dwelling citizens that participated in a municipal home rehabilitation project in Sweden was analysed. A Mann Whitney test and an independent t-test were used to analyse differences within the following assessment instruments: the Sunnaas Activity of Daily Living Index, the General Motor Function assessment scale and the European Quality of Life Five Dimension Five Level Scale. Spearman's bivariate correlation test was used to analyse relationships between the instruments, and a Fischer's Z test was performed to compare the strengths of the correlation coefficients. Result Gender differences were found both within and between the assessment instruments. Women were more independent in instrumental activities of daily living than men. The ability to reach down and touch one's toes while performing personal activities of daily living was stronger for men. There was a difference between men's self-reported performance of usual activities that included instrumental activities of daily living and the standardised assessment in performing instrumental activities of daily living. The result also showed an overall difference between the self-reported assessment and the standardised test of motor function for the total group. Conclusion The results indicate that a comprehensive assessment with the combination of standardised tests, questionnaires and patient-specific instruments should be considered in a home rehabilitation context in order to capture different dimensions of functioning. Assessment instruments that facilitate a person-centred home rehabilitation supporting personally meaningful activities for both men and women should be applied in daily practice. Further research about gender-biased instruments is needed to facilitate agreement on which specific instruments to use at both individual and organisation levels to promote gender-neutral practice.